Dietary resveratrol and β-Hydroxy-β-Methylbutyric acid enhance flavor and modulate intramuscular fat in Tibetan sheep: insights from transcriptomics and lipidomics - Chen, Xuan; Ji, Qiurong; Wu, Zhenling; Zhang, Fengshuo; Su, Quyangangmao; He, Tingli; Zhu, Kaina; Hou, Shengzhen; Gui, Linsheng (Frontiers in Veterinary Science, 2025)
IntroductionThis study investigated the effects of dietary resveratrol (RES) and β-Hydroxy β-Methylbutyrate (HMB) on immune function, oxidative status, and morphological changes in intermuscular fat of Tibetan sheep. Previous research suggests that RES and HMB may enhance muscle quality and lipid metabolism, but their combined effects on meat flavor, fatty acid composition, and underlying molecular mechanisms remain unclear. Therefore, we employed transcriptomics and lipid metabolomics to explore how RES and HMB synergistically regulate key signaling pathways and lipid metabolites to improve meat quality.MethodsA total of 120 male Tibetan lambs with similar initial body weight (15.5 ± 0.14 kg) were randomly divided into four groups (n = 30 per group): 1) H group (basal diet without RES or HMB); 2) H-RES group (1.5 g/day RES); 3) H-HMB group (1.25 g/day HMB); and 4) H-RES-HMB group (1.5 g/day RES + 1.25 g/day HMB). The experiment lasted 100 days, including a 10-day pre-test period and a 90-day formal trial. Intermuscular fat morphology, fatty acid composition, and flavor compounds were analyzed. Transcriptomic and lipid metabolomic approaches were used to identify differentially expressed genes and lipid metabolites, followed by pathway enrichment analysis to elucidate regulatory mechanisms.ResultsThe H-RES-HMB group exhibited significantly reduced intermuscular adipocyte area and diameter (p < 0.05) but increased cell density. Among medium- and long-chain fatty acids, the H-RES-HMB group showed significantly decreased SFAs (C17:0 and C18:0) (p < 0.05) and significantly increased MUFAs (C15:1N5 and C18:1N9) and PUFAs (C18:2N6, C18:3N6, C18:3N3, C20:3N6, and C20:3N3) (p < 0.05). Additionally, flavor compounds such as 2-Hexanone, 3-Hexanone, 3-Pentanone, and Methyl acetate were significantly elevated in the H-RES-HMB group (p < 0.05). Transcriptomic analysis revealed that RES and HMB synergistically regulated the Calcium (ERBB4, P2RX7, ERBB3, P2RX3, and SLC8A1), Hippo (WNT9A, WNT10B, WNT6, and WNT2B), Estrogen (HSP90AA1, TGFA, and RARA), and Arachidonic acid (PLA2G4A, ALOX12, and PTGDS) signaling pathways, collectively promoting muscle cell proliferation and differentiation, Metabolomics identified key lipid molecules (LPC(20:0/20:1), PC(21:2/37:0/38:5)) and pathways (Glycerophospholipid, Arachidonic acid metabolism) contributing to flavor optimization. Integrated analysis highlighted the PLA2G4A-AA-ALOX12/PTGDS axis as a central hub for flavor regulation.DiscussionThe findings demonstrate that RES and HMB synergistically improve meat quality by modulating lipid metabolism and inflammatory responses. The reduction in SFAs and increase in MUFAs/PUFAs align with enhanced nutritional value, while elevated ketones/esters contribute to favorable flavor profiles. The transcriptomic and metabolomic integration reveals that PLA2G4A hydrolyzes PC(38:5) to release AA, which is metabolized via ALOX12/PTGDS to generate flavor precursors (generating 12-HPETE and PGD2). These mechanisms explain the “reduced off-flavor and enhanced aroma” effect. Future studies should validate these pathways in other livestock to assess broader applicability.